Self-Testing of Analog Parts Terminated by ADCs Based on Multiple Sampling of Time Responses - Czaja, Zbigniew (IEEE transactions on instrumentation and measurement, 2013)
A new approach for self-testing of analog parts terminated by analog-to-digital converters in mixed-signal electronic microsystems controlled by microcontrollers is presented. It is based upon a new fault diagnosis method using a transformation of the set of voltage samples of the time response of a tested analog part to a square impulse into localization curves placed in a multidimensional measurement space. The method can be used for fault detection and single soft fault localization. Modified digital Fourier transform formulas are used for conversion of the measurement results to the form used by the fault detection and localization algorithm during the self-testing of the system and also for creation of the fault dictionary. In this paper, the results of experimental verification of the approach are included.